The Relationship between Patient Perception of Service Quality and Polyclinic Revisit Interest - Nurhadiyastuti, Ameilia; Indriyani, Yeni; Agustina, Cynthia; Setyawan, Agus (Journal La Medihealtico, 2025)
The quality of health services encompasses several factors, such as service speed, diagnostic accuracy, facility comfort, the friendly attitude of medical personnel, and patient satisfaction with the services provided. Patient perceptions of service quality play a vital role in building trust and loyalty toward healthcare institutions. According to the 2024 annual report of Ir. Soekarno Regional General Hospital, while there has been a decline in overall patient visits, the number of returning patients has increased. This study aimed to examine the relationship between patient perceptions of service quality and the interest in outpatient re-visits at Ir. Soekarno Regional General Hospital, Sukoharjo Regency. The research used a descriptive quantitative approach with a cross-sectional design. A total of 146 respondents were selected using accidental sampling, determined through the Lemeshow formula based on specific inclusion and exclusion criteria. Data was collected through a questionnaire using a Likert scale, and analysis was performed using Chi-Square tests. The results indicate a significant relationship between the physical dimension (p=0.005) and interest in repeat visits. However, other dimensions such as reliability (p=0.628), personal interaction (p=1.000), problem solving (p=1.000), and policy (p=0.119) showed no significant relationship with outpatient re-visit interest. Overall, the perceived service quality was considered less than optimal, as only the physical dimension influenced repeat visit interest, while other aspects did not. Therefore, it is recommended that the hospital maintain its current physical facilities while focusing on improvements in other service dimensions to enhance patient satisfaction and loyalty.